The Aesteticised Violence - Sułkowska-Janowska, Mariola (Folia Philosophica, 2011)
The article focuses on the problem of moral infertility of the contemporary culture. The phenomenon - the phenomenon of adiaphorization, as Zygmunt Bauman calls it - seems to be a consequence of the process of global anesthetization. The last one is especially noticeable in the context of violence which is submitted for a process of anesthetization in the media. The aforementioned context reveals additionally some socially dangerous consequences of anesthetization as well as of adiaphorization.